Kangaroo Mother Care for Preterm Infants Globally. Issue 3 (May 2015) - Callister, Lynn Clark
Abstract : Kangaroo Mother Care has been identified an important strategy to reduce neonatal mortality in low birth weight and preterm infants globally.